ANÁLISE METAGENÔMICA DE BACTÉRIAS DIAZOTRÓFICAS DE SOLOS ORGÂNICOS DO ESTADO DO PARANÁ - Schneider, Barbara Schaedler Fidelis (2016)
The organic soils from High-Elevation Grasslands of the Parana State are characterized by being large water tanks which fix carbon, have low pH and are poor in nutrients. Though are essential to the Atlantic Forest, there is little information on the microorganisms involved in its maintenance. In this work, microbiological data of organic soils in three different regions, during the dry and rainy seasons were analyzed. Using bioinformatics and statistic tools, nifH gene pirosequences were analyzed to determine the structure of diazotrophic communities and to identify the environmental factors that affect their diversity. The sequences of the nifH gene showed the prevalence of Proteobacteria (35.25%) followed by Spirochaetes (1.27%), Firmicutes (0.80%), Cyanobacteria (0.76%), Chlorobi (0.41%) Actinobacteria (0.10%) and Bacteriodetes (0.04%). Bradyrhizobium was the most abundant genus in the six libraries analyzed, presenting a positive correlation with the increase in the soil pH. Most of nifH gene OTUs showed to be cosmopolitan and the endemism was related to rare species. The OTUs classified as Proteobacteria, Calothrix, Spirochaeta, Halorhodospira, Rhizobiales, Alphaproteobacteria and Bradyrhizobium presented a significant correlation with the rainfall indexes.